STUDI LITERATUR FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN JUMLAH NASABAH PADA BANK SYARIAH - Nurul Fahimah; Fitri Handayani Nasution; Chairina (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Islamic banking is one of the Indonesian banks that has a different system and mechanism than traditional banks, Islamic banks themselves follow the rules and regulations that Islam has long taught, but traditional banks themselves , generally have fixed systems and rules. Continued use of usury (interest) in conducting bond transactions. In banks, marketing is a sure thing. Marketing is the method of conducting business negotiations to attract customers and promotions to obtain results (customers). Well, the customer himself wins by seeing how the bank is doing promotions, value for the price, what kind of competitiveness the customer looking to sign up is looking for. Therefore, an analysis of promotion methods, price bets and competitiveness, whether this will attract the interest of potential customers. to judge.